From the desert to the deserted city: everyday narratives and precarious images images in the work of Elías León Siminiani - Panea, José Luis (Escritura e Imagen, 2024)
The work of filmmaker Elías León Siminiani constantly explores the limits of the audiovisual format. He achieves this through cinematographic montage in a suggestive coexistence between image, both still and moving, and text, both written and narrated, as well as thanks to a minimalist aesthetic marked by a deliberate economy of means, appealing directly and informally to the spectator. In this article I analyse his series “Key Concepts of the Modern world” (1998-2009) as it condenses, embodies and crystallises these strategies, paying special attention precisely to the way in which he develops the aforementioned “concepts” from the documentary essay. In this case, his critical and personal gaze is directed towards the phenomenon of gentrification and the paradoxical loneliness of the individual in an urban and hyper-connected society. The aim is, in short, to highlight this work, which until now has received little attention in the field of criticism and aesthetic reflection, but which takes the pulse of some of the most pressing issues of our time, while at the same time combining the aesthetic concerns of the author who recently won the 37th edition of the Goya Awards.